Strategic Tourism Marketing for Natural Attractions: The Case of Goa Rang Reng Waterfall in Bali, Indonesia - Putrikawati, Made Eni; Saputra, I Made Dian; Yasa, I Ketut Wardana (Darul Yasin Al Sys, 2025)
The tourism sector at Goa Rang Reng Waterfall in Gianyar, Bali, faces challenges such as stagnant visitor numbers due to limited promotion, inadequate infrastructure, and lack of skilled human resources in marketing management. This study aims to develop effective marketing strategies to increase tourist visits while supporting sustainable tourism development. Employing qualitative field research, data were collected through direct interviews with site managers, local community leaders, and tourists, complemented by observational analysis. The findings reveal that enhancing physical facilities, optimizing digital marketing efforts especially via social media and fostering community involvement are critical factors to attract more visitors. Additionally, the site’s unique natural beauty and cultural significance provide a strong foundation for sustainable tourism growth. The study concludes that a comprehensive marketing approach combined with sustainable management practices can significantly improve the destination’s appeal and economic benefits for the local community. These results contribute to tourism management literature by emphasizing the integration of cultural preservation with modern marketing strategies and offer practical implications for similar emerging natural attractions.